Resistance of Hindu Traditionalist Against Sampradaya Hare Krishna Bali - Raudatul Ulum; Lutfi Firdausi (Analisa: Journal of Social Science and Religion, 2021)
This research was conducted to understand the tension between two internal Hindu religious groups in Bali since 1984. The tension shows resistance of Balinese traditional Hindus to the Sampradaya or the spiritualist group of the Hare Krishna consciousness movement. The feud started from a hate speech on social media from both sides that leads to physical persecution. The research was conducted using a case study method, with interviews and observations at the scene and religious practices. This study found out that the conflict was rooted in different religious understandings between the Hare Krishna Gaudy Vaisnava theology and Balinese Hindu Traditional, as well as differences in acceptance of Balinese religious traditions. The contestation of the two parties escalated the feud on social media, then heated up to the closing of Hare Krishna's religious activities. The accumulation of tension was also triggered by religious activities and the appearance of Hare Krishna followers was considered to be in contrast to the Balinese traditional community, and the rite system was considered not to reflect Balinese customs. The research concludes that the institutional interaction between the two parties is deadlocked, although so far there is still a safety valve, namely Nyama Baraya, but the potential for conflict still arises. Similarity of ethnic background; dialogue intentions do not find common ground, the reintegration process is threatened with failure. A solution through dialogue is still the best step compared to resolving power or law enforcement, therefore efforts to bring the two parties together in dialogue must continue.